Realist evaluation for programs and services in the health area: an integrative review of the theoretical and methodological literature - Jeane Roza Quintans; Tatiana Yonekura; Carla Andrea Trapé; Cassia Baldini Soares (Revista Latino-Americana de Enfermagem, 2020)
Objective: to identify and analyze the concepts of the realist evaluation and the methodologies recommended for its development in the health area. Method: an integrative review, which included theoretical and methodological studies published in the following databases: COCHRANE Library, EVIPNet, Health Systems Evidence, LILACS, PDQ-Evidence, PubMed, Rx for Change, and SciELO, in addition to Teses-CAPES and Google Scholar, for the gray literature. The mediation category underlay the analysis. Results: 19 references were included, published between 1997 and 2018. It is an innovative proposal to direct the process of evaluating health programs, interventions, and/or policies, with the democratic participation of the parties involved, such as users, workers, managers and researchers; it proposes to elaborate theories about what works, for whom, in what context, and how. The mediation category indicated the need for these theories not to be restricted to the micro-context, but to incorporate the elements of the social macro-structure to which they are connected. Conclusion: It is indicated that the realist evaluation is to be conducted in 21 stages. It takes into account qualitative and procedural methods, which makes it powerful for understanding human and social relationships in the context analyzed. Theories that come from evaluating the functioning of the programs analyzed have greater explanatory chances if they are built by reference to the social totality.